ANALYSIS OF THE FINANCIAL PERFORMANCE OF RSUD ANUTAPURA PALU BEFORE AND DURING COVID 19 - Jumiati; Muslimin; Kadang, Juliana (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
This type of research is descriptive quantitative research with the trend analysis method / time series analysis which focuses on knowing and analyzing the financial performance of the Regional Public Service Agency of the Anutapura Palu Regional General Hospital before and during the Covid 19 pandemic from the aspects of liquidity, activity aspects, profitability aspects, and aspects of PNBP income to operational costs. The research method using descriptive is a research method carried out to focus on the main objective of objectively describing and describing the situation. This research describes the calculation of financial ratios and uses the analysis of liquidity ratios, activity ratios, profitability ratios and PNBP revenue ratios at Anutapura Palu Hospital for the period 2017-2022. The financial reporting period in 2017 until 2019 was chosen because this year the condition of Anutapura Palu Hospital has not been affected by the Covid 19 pandemic. The financial report for 2020 to 2022 was chosen because this year Anutapura Palu Hospital has been affected by the Covid 19 Pandemic. Financial ratio analysis shows that during the Covid 19 pandemic, management performance to generate surplus to the hospital has decreased compared to before the Covid 19 pandemic. Continuous performance evaluation is essential to ensure the continuity of sustainability and improvement in the quality of hospital services.